Timing of CSF-1/CSF-1R signaling blockade is critical to improving responses to CTLA-4 based immunotherapy. (2nd July 2016) - Holmgaard, Rikke B.; Brachfeld, Alexandra; Gasmi, Billel; Jones, David R.; Mattar, Marissa; Doman, Thompson; Murphy, Mary; Schaer, David; Wolchok, Jedd D.; Merghoub, Taha
ABSTRACT: Colony stimulating factor-1 (CSF-1) is produced by a variety of cancers and recruits myeloid cells that suppress antitumor immunity, including myeloid-derived suppressor cells (MDSCs.) Here, we show that both CSF-1 and its receptor (CSF-1R) are frequently expressed in tumors from cancer patients, and that this expression correlates with tumor-infiltration of MDSCs. Furthermore, we demonstrate that these tumor-infiltrating MDSCs are highly immunosuppressive but can be reprogrammed toward an antitumor phenotype in vitro upon CSF-1/CSF-1R signaling blockade. Supporting these findings, we show that inhibition of CSF-1/CSF-1R signaling using an anti-CSF-1R antibody can regulate both the number and the function of MDSCs in murine tumors in vivo . We further find that treatment with anti-CSF-1R antibody induces antitumor T-cell responses and tumor regression in multiple tumor models when combined with CTLA-4 blockade therapy. However, this occurs only when administered after or concurrent with CTLA-4 blockade, indicating that timing of each therapeutic intervention is critical for optimal antitumor responses. Importantly, MDSCs present within murine tumors after CTLA-4 blockade showed increased expression of CSF-1R and were capable of suppressing T cell proliferation, and CSF-1/CSF-1R expression in the human tumors was not reduced after treatment with CTLA-4 blockade immunotherapy. Taken together, our findings suggest that CSF-1R-expressing MDSCs can be targeted to modulate the tumor microenvironment and that timing of CSF-1/CSF-1R signaling blockade is critical to improving responses to checkpoint based immunotherapy. Significance: Infiltration by immunosuppressive myeloid cells contributes to tumor immune escape and can render patients resistant or less responsive to therapeutic intervention with checkpoint blocking antibodies. Our data demonstrate that blocking CSF-1/CSF-1R signaling using a monoclonal antibody directed to CSF-1R can regulate both the number and function of tumor-infiltrating immunosuppressive myeloid cells. In addition, our findings suggest that reprogramming myeloid responses may be a key in effectively enhancing cancer immunotherapy, offering several new potential combination therapies for future clinical testing. More importantly for clinical trial design, the timing of these interventions is critical to achieving improved tumor protection.